ANALYSIS OF LIQUIDITY, SOLVENCY, AND ACTIVITY RATIOS ON FINANCIAL PERFORMANCE (Empirical Study of Iron and Steel Industry Companies Listed on the Indonesia Stock Exchange 2022-2024) - Ikhsan Sidiq Febriansyah; Ardian Prima Putra (MANAJEMEN DEWANTARA, 2026)
This study investigates the effect of liquidity, solvency, and activity ratios on the financial performance of iron and steel companies listed on the Indonesian Stock Exchange (IDX) during 2022–2024. Liquidity is represented by the current ratio (CR), solvency is measured using the debt-to-equity ratio (DER), and activity is captured by the total asset turnover ratio (TATO). Financial performance is proxied by return on equity (ROE).A quantitative research approach was employed, utilizing multiple linear regression analysis on secondary data obtained from the annual financial statements of the companies. The study analyzed a total of 108 firm-year observations. The empirical results indicate that the current ratio does not have a significant effect on return on equity, suggesting that short-term liquidity alone is insufficient to directly enhance profitability. In contrast, both the debt ratio and total asset turnover exhibit a significant positive relationship with return on equity. These findings imply that effective asset management and an appropriate capital structure are crucial factors in improving financial performance. Furthermore, the coefficient of determination shows that approximately 51.1% of the fluctuations in return on may be defined with the aid of the mixed impact of liquidity, solvency and activity ratios. Overall, the results underscore the decisive role of investment efficiency, leverage management and working capital management in strengthening the financial capacity of steel companies. Keywords : financial performance (ROE); activity ratios (TATO); liquidity ratios (CR); and solvency ratios (DER).